The Integration of Residential Real Estate Market and Stock Markets : Assessment from ARDL Approach - Wong, Woei Chyuan (2005)
This thesis examines the long-run and short-run relationship between residential real estate market and stock market in Malaysia during the period of 1988-2004. I take the perspective that real estate prices are the driving forces of stock prices given the fact that the purchase of residential property is an important investment decision to an individual investor. Individual investors are expected to adjust their financial assets allocation based on the changes in house prices with the purpose to maximize their investment utility. Terrace House Price Index and High-Rise Unit Price Index were used as proxies for residential real estate market given the trade-off nature between these properties for an individual investor when come to investment decision. By using Autoregressive Distributed Lag (ARDL) cointegration procedure, the results suggest that residential real estate and stock market are not cointegrated. Further test was also executed by using the All House Price Index as a proxy for residential real estate. The results remained the same where residential real estate market is found to be segmented from the stock market. An exclusian of a variable (Consumer Price Index) that was highly correlated with other independent variables in the ARDL model also does not change the results. This would indicate that investors could diversify their portfolio by investing in the residential real estate and the stock market.